Cycloaddition-based approaches to nor-taxoids and aphenes via magnesium- and indium-mediated reactions - Husk, Elizabeth (University of Ottawa (Canada), 2004)
Various synthetic routes were used in attempt to synthesize nortaxoids that have the potential to be more potent anti cancer reagents than TaxolRTM. In a previously established pathway to taxoid precursor 66, aldehyde 65 was difficult to purify and store. An alternative method involved preparing enol ether 79 using carbometallation and Wittig chemistry. An attempted synthesis of nortaxoid 97 used indium chemistry as a key step in its synthetic pathway. The chemical properties of aphenes are not known as well as those of acenes. Acenes are known to have interesting electronic properties. The electronic utility of aphenes is not known. The diene-transmissive Diels-Alder reaction of cross-conjugated trienes with cyclic dienophiles was used to make the skeleton of butaphene precursor (190). The conversion of these skeletons, which can act as dienophiles, into hexaphenes 204 or octaphenes 205 through a second Diels-Alder reaction with cyclic dienes (i.e. cyclopentadiene or o-quinodimethane was investigated. (Abstract shortened by UMI.)
Keywords: Chemistry, Organic.